Intraocular hemorrhage in patients misdiagnosed with central retinal artery occlusion treated with thrombolysis - Daniel V. Adamkiewicz; Christian Leal; Kevin Y. Yan; Sruthi Arepalli; Kevin Ferenchak; Blaine Cribbs; Riley J. Lyons; Étienne Bénard-Séguin; Étienne Bénard-Séguin; Étienne Bénard-Séguin; Nancy J. Newman; Nancy J. Newman; et al. (Frontiers in Neurology)
IntroductionThe diagnosis of acute central retinal artery occlusion (CRAO) is commonly delayed in emergency departments (ED) where ophthalmologists are rarely available for immediate consultation. Thrombolysis is sometimes given empirically for presumed CRAO without confirmation of the diagnosis with ocular funduscopic examination.MethodsWe describe one case of severe intraocular hemorrhage following intravenous thrombolysis for a retinal detachment misdiagnosed as a CRAO, and two cases of worsening intraocular hemorrhage following intravenous thrombolysis for misdiagnosed CRAO, and review the literature.ResultsWe identified 4 cases in the literature were thrombolysis given for RAO resulted in ocular hemorrhage. We identified 12 additional cases where thrombolysis given for any indication resulted in intraocular hemorrhage.DiscussionOcular hemorrhage is a rare but potentially devastating complication of thrombolysis in patients with underlying retinal disorders other than CRAO. Thrombolysis should never be given for acute vision loss without a funduscopic examination or ocular imaging confirming the diagnosis of CRAO.